IMPLEMENTASI PERDA NO 14 TAHUN 2011 TENTANG RENCANA TATA RUANG WILAYAH (RTRW) KOTA SEMARANG (STUDI KASUS PEMBATASAN LAHAN UNTUK PERUMAHAN DI ATAS PERBUKITAN) - Johanita Ardhiasri; Zaenal Hidayat; Dewi Rostyaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Semarang population growth increasing impact the growing need for housing . Housing is comfortable , safe and free society yearning flood the city, so that the hills become an alternative development of new settlements . Housing in the hills now have proliferated , it has become a new problem for the hills designated as a buffer zone of Semarang . Thus, in Regulation No. 14 of 2011 are mentioned in Article 119 of the restriction of land for housing in the hills . The purpose of this study is to investigate the implementation of Regulation No. 14 Year 2011 about Spatial Plan of the city, as well as to determine the factors that hinder the implementation of the policy . The formulation of the problem in this research is about how the implementation of the Regulation No. 14 of 2011 and what are the factors that hinder the implementation of the regulation. This study used a qualitative research method because that will be examined are many phenomena that occur at the sites as well as an analysis of the relationship between the observed phenomenon . With this type of research is expected to get an overview of descriptive analysis in a systematic , factual and accurate information on the facts and the relationship between the phenomenon under study . Determination of the informants in this study using purposive sampling where the determination of informants chosen with special consideration of the researcher. The results of this research is the implementation of spatial planning policy has shifted very significant because most of Semarang space development policy is not in accordance with the land designated function . Interactions were constructed by policy makers actually prefer the interests of the public rather than the use of space that is expected to be affected by the use or management of space . While the factors that hinder the implementation of the Regulation on spatial planning is the lack of public interest a government priority ; existence of private parties that violate applicable laws ; yet supports adequate resources ; lack of concrete measures from the government to crack down on violations ; law is an advanced rules and procedures are already in the previous period so as to improve the system is not an easy thing.